Structural underpinnings of Ric8A function as a G-protein α-subunit chaperone and guanine-nucleotide exchange factor - Dhiraj Srivastava (Nature Portfolio, 2019)
Ric8A regulates G protein α-subunits (Gα) by acting as a guanine nucleotide exchange factor (GEF) and a Gα chaperone. Here, the authors solve the crystal structures of free and Gα fragment bound Ric8A, and provide insights into the structural basis for Ric8A’s GEF and chaperone functions.